Phase-Contrast and Dark-Field Imaging - Simon Zabler (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The intent of this Special Issue is to provide a framework with which scientists in several different disciplines, related to phase-contrast and dark-field imaging, can illustrate their ideas and results. The articles are reviews or very recent scientific reports; they address newcomers in the field, as well as experts and professors in fields of X-ray physics, electron, and phase-contrast X-ray imaging.